2018
DOI: 10.1108/jmd-04-2017-0135
|View full text |Cite
|
Sign up to set email alerts
|

Training for the coaching leader: how organizations can support managers

Abstract: Purpose The demand for leaders to coach their employees is increasing as the benefits become more and more evident. However, little is known about the training managers have received in coaching or what support is available/required from their organizations. The paper aims to discuss this issue. Design/methodology/approach The paper encompassed a survey of 580 managers in Australian organizations with more than 200 employees. The authors used qualitative thematic analysis to examine the extensive free text a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 37 publications
0
79
0
Order By: Relevance
“…Grounded theoretically in coaching leadership theory, this recently form of leadership has been defined as a day-to-day process of providing support, and helping employees identify opportunities to achieve individual development goals (Cox et al, 2010;Berg and Karlsen, 2016). Leaders who succeed with a coaching style enable employees to gain awareness and reflection, generate their own answers (Cox et al, 2010;Milner et al, 2018), require less control and directing, and have a desire to help them develop and flourish (Berg and Karlsen, 2016). Goleman et al (2012) suggested that coaching is one of the leadership styles that achieves the best results, and that its main purpose is to develop employees' personal resources.…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
See 4 more Smart Citations
“…Grounded theoretically in coaching leadership theory, this recently form of leadership has been defined as a day-to-day process of providing support, and helping employees identify opportunities to achieve individual development goals (Cox et al, 2010;Berg and Karlsen, 2016). Leaders who succeed with a coaching style enable employees to gain awareness and reflection, generate their own answers (Cox et al, 2010;Milner et al, 2018), require less control and directing, and have a desire to help them develop and flourish (Berg and Karlsen, 2016). Goleman et al (2012) suggested that coaching is one of the leadership styles that achieves the best results, and that its main purpose is to develop employees' personal resources.…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
“…According to the International Coach Federation (n.d.), the leading global coaching organization, essential coaching competencies consist of establishing trust and a working alliance, active listening, powerful questioning, direct communication, designing actions and goal setting, and managing progress. In using coaching skills, leaders enable employees to generate their own answers, thus enhancing development and performance (Grant and O'Connor, 2010;Milner et al, 2018). In the current study, we follow previous literature and research related to the professional coach's skills, the leader-as-coach, and managerial coaching, in order to identify eight core coaching-based leadership skills classified into four dimensions: (a) working alliance: developing a working alliance (1); (b) open communication: active, empathic, and compassionate listening (2), and powerful questioning (3); (c) learning and development: facilitating development (4), providing feedback (5), and strengths spotting and development (6); and (d) progress and results: planning and goal setting (7), and managing progress (8).…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%
See 3 more Smart Citations